Jonathan Harris. The lost world of Byzantium - Intagliata, Emanuele E. (Journal of Greek Archaeology, 2017)
The lost world of Byzantium is a rather agile and engaging read covering the history of the Byzantine Empire from the foundation of Constantinople to its fall by the hands of Sultan Mehmet II in 1453. The principle aim, as part of the wider scope of the work, is ‘to investigate why Byzantium lasted for so long, in spite of all the upheavals and invasions that threatened its existence’ (preface, p. x). The ten chapters dedicated to this purpose are structured chronologically; each chapter starts with an excerpt from a written source, a hint on the main lens through which the historical facts are to be examined. The history of Byzantium is recounted by those prominent figures that directly acted to make the empire great, or that brought it to its collapse. It is a history, then, made by emperors, generals, courtiers, and patriarchs, described from the centre (Constantinople), and where the middle and lower classes are mentioned rarely, if at all.